Data from: The evolutionary history of dogs in the Americas - Leathlobhair, Máire Ní; Perri, Angela R.; Irving-Pease, Evan K.; Witt, Kelsey E.; Linderholm, Anna; Haile, James; Lebrasseur, Ophelie; Ameen, Carly; Blick, Jeffrey; Boyko, Adam R.; Brace, Selina; Nunes Cortes, Yahaira; et al. (Zenodo, 2019)
Dogs were present in the Americas prior to the arrival of European colonists, but the origin and fate of these pre-contact dogs are largely unknown. We sequenced 71 mitochondrial and seven nuclear genomes from ancient North American and Siberian dogs spanning ~9,000 years. Our analysis indicates that American dogs were not domesticated from North American wolves. Instead, American dogs form a monophyletic lineage that likely originated in Siberia and dispersed into the Americas alongside people. After the arrival of Europeans, native American dogs almost completely disappeared, leaving a minimal genetic legacy in modern dog populations. Remarkably, the closest detectable extant lineage to pre-contact American dogs is the canine transmissible venereal tumor, a contagious cancer clone derived from an individual dog that lived up to 8,000 years ago. Mitochondrial DNA FASTA file FASTA file containing 1166 dog mtDNA genomes used in this study full_mtDNA_alignment.fasta NEXUS tree Maximum likelihood tree (RAxML) of 1166 dogs mtDNA genomes used in this study full_mtDNA_alignment.tre Excel sheet Publication source of the 1166 mtDNA genomes used in this study full_mtDNA_alignment.xlsx Plink (bed) file Contains genotype for dogs 54 dogs full_data.bed Plink file (bim) Contains genotype for 54 dogs full_data.bim Plink file (fam) Contains genotype for 54 dogs full_data.fam NJ tree in Figure 2b NJ tree in Figure 2b (see Table S2 for more info) Figure_b.tre Nexus file Nexus file used for producing Figure S12 (MKV model in MrBayes) Binary_char_MKV.nex NEXUS tree Bayesian tree in Figure S12 (see Table S2 for more info) Figure_S12.tre